Migration and modernities : the state of being stateless, 1750-1850 - DeLucia, JoEllen; Shields, Juliet, 1976- (Edinburgh University Press, 2019)
This collection initiates transnational, transcultural and interdisciplinary conversations about migration in the 18th and 19th centuries.
Also issued in print: 2019.
Keywords: Emigration and immigration in literature.; Immigrants in literature.; Colonization in literature.; English literature -- 18th century -- History and criticism.; English literature -- 19th century -- History and criticism.; American literature -- 18th century -- History and criticism.; American literature -- 19th century -- History and criticism.; Émigration et immigration dans la littérature.; Immigrants dans la littérature.; Colonisation dans la littérature.; Littérature anglaise -- 18e siècle -- Histoire et critique.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Littérature américaine -- 18e siècle -- Histoire et critique.; Littérature américaine -- 19e siècle -- Histoire et critique.; HISTORY / Modern / 18th Century; American literature; Colonization in literature; Emigration and immigration in literature; English literature; Immigrants in literature; 1700-1899; Criticism, interpretation, etc.